Immunoexpression of tumor suppressor protein p53 and deubiquitinating enzymes in oral squamous cell carcinoma - Jussara Maria Gonçalves; João Luiz Dornelles Bastos; Elena Riet Correa Rivero; Mabel Mariela Rodríguez Cordeiro (Revista Sul-Brasileira de Odontologia, 2022)
The ubiquitin-proteasome system is regulated by deubiquitinating enzymes (DUBs), which include the complex Ubiquitin-specific protease 1 (USP1) and WD40 repeat-containing protein 48 (WDR48). In normal conditions, these proteins contribute to genome integrity by regulating the DNA repair pathways. However, studies have associated abnormalities in this complex with the pathogenesis of cancer. Simultaneously, Tumor Suppressor Protein p53 is also regulated by ubiquitin-dependent degradation and its overexpression suggests that several DUBs are interacting and deubiquitinating this protein. Objective: To evaluate the immunoexpression of p53, USP1, and WDR48 in Oral Squamous Cell Carcinoma (OSCC). Material and methods: Thirty cases of OSCC and 40 non-neoplastic oral epithelium (NNOE, control group) were selected for immunohistochemical investigation. The histopathological classification was performed using H&E-stained sections. Values were statistically analyzed using the non-parametric test Kruskal Wallis. Results: Higher positivity of the markers was found in OSCC (p53:65%; USP1:96.4%; WDR48: 68.9%) than in NNOE (p53:35.1%; USP1:85%; WDR48: 65.2%). Poorly-differentiated cases of OSCC exhibited higher nuclear immunostaining of all proteins when compared with well-differentiated samples. Conclusion: This is a pioneer study and suggests that p53 and deubiquitinating enzymes (USP1 and WDR48) can affect the biological behavior of OSCC as they are related to the tumor development and histological malignancy grading.